Obesity and the built environment - Booth, Katie M.; Pinkston, Megan M.; Poston, Walker S. Carlos (My University, 2013)
Biological, psychological, behavioral, and social factors are unable to fully explain or curtail the obesity epidemic. The goal of this paper is to provide a review of research on the influence of the built environment on obesity. Studies were evaluated with regard to their methods of assessing the environment and obesity, as well as to their effects. Methods used to investigate the relationships between the built environment and obesity were found to be dissimilar across studies and varied from indirect to direct. Levels of assessment between and within studies varied from entire counties down to the individual level. Despite this, obesity was linked with area of residence, resources, television, walkability, land use, sprawl, and level of deprivation, showing promise for research utilizing more consistent assessment methods. Recommendations were made to use more direct methods of assessing the environment which would include specific targeting of institutions thought to vary widely in relation to area characteristics and have a more influential effect on obesity-related behaviors. Interventions should be developed from the individual to the neighborhood level, specifically focusing on the effects of eliminating barriers and making neighborhood level improvements that would facilitate the elimination of obesogenic environments.
Keywords: Obesity; Built environment